Perlindungan Hukum terhadap Whistleblower dalam Tindak Pidana Narkotika. - Gusti Nyoman Adung Setiawan; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2021)
A wistleblower is someone who is aware of a criminal act and notifies it to law enforcement officials. The role of whistleblowers is very important to help expose acts of narcotics abuse. The purpose of this study is to determine the legal protection arrangements for whistleblowers in narcotics abuse and to find out legal protection for whistleblowers in narcotics crime. The research method used in this research is normative legal research method normative legal research method which is carried out by examining a statutory regulation related to the problem being discussed and through a conceptual approach or conceptual approach which shows a concept, and uses a conceptual approach. doctrine, namely the views or thoughts of experts related to the science of law. A person who is a whistleblower or notifier in narcotics abuse always bears a reply from those who feel aggrieved or aggrieved as a result of a notification or report from a whistleblower, legal security for a person who is a pioneer or whistleblower in investigating criminal acts of narcotics abuse is important given to the authorities so that all people are willing to become reporters in order to support legal institutions to reveal and arrest narcotics abuse. Security for whistleblowers must be made strictly in law so that security for whistleblowers can be upheld.